An investigation of the effects of a moral education program on the ethical development of Malaysian future accountants - Mohamed Saat, Maisarah (Curtin University, 2010)
This longitudinal study investigates the ethical development of Malaysian accounting students after completion of a moral education program (MEP) that includes an ethics course and subsequent practical training. Emphasis is placed on the examination of two moral cognitive processes, ethical sensitivity and ethical judgement making ability. The study involves three phases of data collection, prior to an ethics course, after an ethics course and after practical training. It also determines whether there are differences in the ethical development at the post ethics course between religious affiliation, faith maturity, type of institution (public or private), and academic performance. The study also examines whether the content and teaching process of an ethics course influences students’ sensitivity and reasoning abilities.The data collection involves distribution of questionnaires to students over the three phases of the study and one to ethics lecturers. The student questionnaires consist of vignettes developed by Longenecker et al. (1989) to measure ethical sensitivity while Rest’s (1986) Defining Issues Test (DIT) was used to gauge students’ ethical judgement making ability. Information related to the way an ethics course is taught in different universities were collected from the questionnaire to the ethics lecturers and by examining the ethics syllabi. In the final sample, data from six universities was collected and analysed; two public and two private which provide an ethics course (experiment group), and two universities who do not provide a course (control group). Statistical analyses such as paired tests, factor analysis, regression and correlation were used. General Linear Model Repeated Measures was run to determine the effect of the MEP on the improvement of ethical sensitivity and judgement making ability involving the three phases of data.Results show that students’ ethical sensitivity and judgement making ability significantly improved after attending an ethics course. Muslim students, students from public universities and students with good and average academic performance were found to improve significantly in ethical sensitivity upon completing the course. Students from ‘Other’ religions, students from private universities and students with excellent academic performance show significant improvement in judgement making ability. Analyses also show that certain characteristics of course objectives, content and expertise produced varying degrees of improvement in ethical sensitivity and judgement making ability. Findings from the third phase data demonstrated that students who undertake practical training did not improve in their ethical sensitivity but improved significantly in their ethical judgement making ability. Students who were assigned various types of tasks improved significantly in their reasoning ability compared to students who focused on a single task. Importantly, results indicate that a MEP significantly improved students’ ethical sensitivity and judgement making ability.This thesis has made an original contribution to Malaysian accounting research by identifying the benefits of an ethics course, practical training and a MEP on ethical sensitivity and ethical judgement making ability and confirming the theory that education and a socialization process influences ethical development. The implication for Malaysian universities and policy makers in particular is that the results strongly recommend that an ethics course should be introduced in all Malaysian universities offering accounting degrees. Among suggestions to improve the teaching of an ethics course is the inclusion of experiential methods and emphasis on a balance of rule based concepts and theoretical and philosophical issues. As social interaction related to wider non-focused tasks during practical training has a more significant influence than focused training, the study recommends that practical training should be conducted in an unfocused task manner where students are exposed to a variety of tasks and potentially a broader circle of socialisation structures and ethical situations.